2009
DOI: 10.1519/jsc.0b013e318196b7c6
|View full text |Cite
|
Sign up to set email alerts
|

Determining Variables of Plyometric Training for Improving Vertical Jump Height Performance: A Meta-Analysis

Abstract: Plyometric training improves vertical jump height (VJH). However, the effectiveness of plyometric training depends on various factors. A meta-analysis of 56 studies with a total of 225 effect sizes (ESs) was carried out to analyze the role of various factors on the effects of plyometrics on VJH performance. The inclusion criteria for the analysis were a) studies using plyometric programs for lower-limb muscles, b) studies employing true experimental designs and valid and reliable measurements, and c) studies i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
258
7
23

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 268 publications
(311 citation statements)
references
References 44 publications
23
258
7
23
Order By: Relevance
“…External resistance can be added to the vertical jump to increase the intensity of the training stimulus (33). The most common methods of applying resistance include the use of barbells, dumbbells, weighted vests and rubber bands.…”
Section: Introductionmentioning
confidence: 99%
“…External resistance can be added to the vertical jump to increase the intensity of the training stimulus (33). The most common methods of applying resistance include the use of barbells, dumbbells, weighted vests and rubber bands.…”
Section: Introductionmentioning
confidence: 99%
“…38,41 Other assessment measures that future researchers may want to consider as an alternative to the Max Power Test are the 1-rep-max (1RM) leg press, a measure of lower body strength, 9 or the vertical jump, a measure of lower body power. 6,30 Another limitation of this study is that other factors that may impact performance were not monitored, such as caffeine consumption 42 and menstruation. 43 In addition, stress and anxiety levels themselves were also not measured, which would have strengthened this study considerably.…”
Section: Limitationsmentioning
confidence: 99%
“…plyometrics or resistance training) over an extended period of time (e.g. weeks to months), 29,30 therefore it is presumed that the test-retest reliability of the Max Power Test would be sufficient, although no specific study was found to support this.…”
Section: Clinical Seriesmentioning
confidence: 99%
“…O exercício drop jump e suas variações são frequentemente incorporados às rotinas do treinamento de modalidades dependentes da produção de potência nos membros inferiores [1][2][3] . O drop jump é caracterizado pela queda de uma altura pré-determinada, seguida imediatamente de um salto máximo.…”
Section: Introductionunclassified
“…A manipulação da altura de queda é considerada como a principal maneira de controlar a intensidade do exercício afetando diretamente o desempenho final 5,7,8 . A fim de maximizar a intensidade do exercício, a literatura sugere que a altura de queda seja individualizada, sendo sempre utilizada aquela que garanta maior altura de salto 3,9,10 . Por outro lado, entende-se que a utilização de uma grande intensidade gera maior estresse mecânico, e que pode, no treinamento, estar associado a uma grande frequncia de estímulos repetidos, ocasionando maior probabilidade de lesões no tecido biológico dos membros inferiores 5 .…”
Section: Introductionunclassified